STUDENTS' MATHEMATICAL REPRESENTATION ABILITY IN LEARNING OF MATHEMATICAL MODELING USING ANDROID-BASED LEARNING MEDIA - Otniel, Otniel; Kurniadi, Elika (Jurnal Pendidikan Matematika (JUPITEK), 2024)
Mathematical representation ability is one of the important mathematical abilities for students to have because this ability plays an important role in students' ability to solve problems. This research is a descriptivequalitative research that aims to see students' mathematical representation skills in learning mathematical modeling using android-based learning media. The instruments used in this study were test questions in the form of mathematical modeling essay questions and interview guidelines. Students' mathematical representation ability was measured based on indicators of mathematical representation ability, namely visual representation, mathematical expression representation, and verbal representation. Based on the results of data analysis, it was concluded that the representation ability of students had a Very Good category of 63%, a Good category of 20%, and a Fair category of 17%. Students with Very Good category can do mathematical representation well as a way to help them in doing problem solving. Most of students in the Good category can make mathematical representations well, but still make a few mistakes in counting and understanding the problem. Most of students in the Fair category can make visual representations, but have not been able to do mathematical expression representations or verbal representations optimally.